Super capacitor positive electrode material and preparation method and application thereof

By using carbon material with a channel and a microcrystalline structure as the positive electrode material of the supercapacitor and matching it with the lithium titanate negative electrode material, the problem of insufficient specific capacity and electronic conductivity of the positive electrode material in the prior art is solved, and a supercapacitor with high energy density and high power density is realized.

CN119626788APending Publication Date: 2025-03-14QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411721433.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The specific capacity and electronic conductivity of the existing supercapacitors are low, resulting in insufficient power density and energy density, and when matching the capacity of the negative electrode material, it brings huge challenges to the electrode sheet coating technology.

Method used

Carbon materials with pore channels and microcrystalline structures are used as the positive electrode material, and pore formation and high temperature treatment are used to form porous carbon materials with high specific surface area and electronic conductivity, and are combined with lithium titanate negative electrode material to build a lithium titanate-based supercapacitor.

Benefits of technology

The specific capacity and electronic conductivity of the positive electrode material are significantly improved, the coating difficulties caused by matching the positive and negative electrode capacity is reduced, and the energy density and power density of the supercapacitor are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626788A_ABST
    Figure CN119626788A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical energy storage, and particularly relates to a supercapacitor positive electrode material and a preparation method and application thereof. The positive electrode material is a carbon material with a pore channel and a microcrystalline structure, the particle size D50 is 2-8 [mu] m, the specific surface area is 50-300 m < 2 > / g, the intensity ratio ID / IG of a disordered degree D peak to an ordered degree G peak in a Raman spectrogram is 0.9-1.1, the ordered stacking height LC of the carbon material microcrystalline in the z-axis direction calculated according to the half-peak width of a (002) peak in an X-ray diffraction pattern is 3-10 nm, and the ordered stacking height LC of the carbon material microcrystalline in the z-axis direction calculated according to the half-peak width of the (002) peak in the X-ray diffraction pattern is 3-10 nm. The average width La of the carbon material microcrystal in the a-axis direction calculated by a (100) peak is 5-20 nm, the specific capacity is 100-150 mAh / g, and the electronic conductivity is 5-10 S / cm. The preparation method of the positive electrode material comprises the steps of carbonization, pore forming and high-temperature treatment. When the positive electrode material is applied to the lithium titanate-based super capacitor, the problem that the electrode material is difficult to coat on a current collector due to capacity matching of the positive electrode and the negative electrode can be greatly solved, and meanwhile, the energy density and the power density are synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a supercapacitor positive electrode material and a preparation method and application thereof. Background Art

[0002] As the world attaches great importance to climate change and energy conservation and carbon reduction, the new energy industry has become one of the strategic emerging industries in the new century. As an important support and auxiliary technology for the new energy industry, the new energy storage material industry has attracted much attention from all parties. In my country, with the rapid development of pure electric vehicles and hybrid vehicles, the steady advancement of smart grids, the large-scale access of renewable energy such as wind and solar energy to the grid, and the growth of regional peak loads, various application problems have also emerged, which have put forward higher requirements for the energy density, power density and service life of electrochemical energy storage devices.

[0003] Supercapacitors have the characteristics of high power density and long cycle life. A typical example is a double-layer supercapacitor, whose positive and negative active materials are porous carbon. When charging, the high specific surface area of ​​the porous carbon (usually 1000-2500m 2 / g) to physically adsorb charges for energy storage. The specific capacity of porous carbon for storing charges is ~50mAh / g. The power density of double-layer supercapacitors is ≥5kW / kg and the charge-discharge cycle life is 100,000 times, but its energy density is low (mass energy density: ~5Wh / kg, volume energy density ~15Wh / L). The second is lithium-ion supercapacitors, whose positive active material is porous carbon and negative active material is graphite. When charging, the positive electrode stores electrical energy by physically adsorbing charges, and the negative electrode stores electrical energy by electrochemically inserting lithium. Its power density is ≥5kW / kg, and its charge and discharge cycle life is 50,000 times. The energy density has been improved to 15-20Wh / kg, but the energy density is still low. In addition, the specific capacity of graphite for lithium insertion of the negative active material is ~350mAh / g, which is much higher than the specific capacity of porous carbon for adsorbing anions of ~50mAh / g. Under the same weight, the capacity of the negative electrode is 7 times that of the positive electrode. Therefore, the positive electrode needs to be 7 times heavier than the negative electrode to achieve capacity matching, which brings great challenges to the electrode coating technology. In order to achieve positive and negative electrode capacity matching, previous technologies often pre-lithiate the negative active material graphite, which undoubtedly increases the complexity and cost of lithium-ion supercapacitor production.

[0004] It has been reported that high specific surface area porous carbon is used as the positive electrode active material, lithium titanate (Li4Ti5O 12, abbreviated as LTO) as the negative electrode active material, a lithium titanate-based supercapacitor is constructed. However, the specific capacity of porous carbon physically adsorbing charges is ~50mAh / g, and the specific capacity of lithium titanate electrochemical lithium insertion is ~160mAh / g. The capacity difference between the two is large. In order to match the capacity of the negative electrode, the positive electrode needs to be coated with 3 times the weight of the negative electrode active material, which also brings challenges to the electrode coating technology. In addition, the electronic conductivity of high specific surface area porous carbon is ~0.8S / cm, which is not conducive to improving power performance. Therefore, it is of great significance to develop new positive electrode materials and supercapacitors composed of them with high energy density and high power density. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a supercapacitor positive electrode material and application.

[0006] To achieve the above purpose, the present invention adopts the following technical solution:

[0007] A supercapacitor positive electrode material, the positive electrode material is a carbon material with pores and microcrystalline structure, the particle size D50 is 2 to 8 μm, and the specific surface area is 50 to 300 m 2 / g, in the Raman spectrum, the intensity ratio of the disordered D peak to the ordered G peak is D / I G is 0.9 to 1.1, and the ordered stacking height L of the carbon material crystallites along the z-axis direction calculated from the half-peak width of the (002) peak in the X-ray diffraction pattern C The carbon material has an average crystallite width La of 3 to 10 nm along the a-axis direction calculated from the (100) peak, a specific capacity of 100 to 150 mAh / g, and an electronic conductivity of 5 to 10 S / cm.

[0008] The positive electrode material is a carbon material having pores and a microcrystalline structure formed by carbonizing a precursor material, forming pores and undergoing high-temperature treatment.

[0009] Further,

[0010] (1) Carbonization: The cathode material precursor is placed in a medium temperature furnace protected by an inert gas at 500-700°C for carbonization for 0.5-2 hours, and then taken out after cooling to obtain a carbonized material;

[0011] (2) Pore formation: the pore former is dissolved in deionized water to form a pore former solution, the carbonized material is stirred and dispersed in the pore former solution and fully impregnated, and then placed in a medium temperature furnace protected by inert gas at 600-800°C for 0.5-2h, cooled, washed and dried to obtain a porous carbon material with a high specific surface area;

[0012] (3) High temperature treatment: The obtained porous carbon material is placed in a high temperature furnace protected by inert gas at 1600-2200°C for 0.5-2h. After cooling, it is taken out and then graded by a cyclone separator to obtain a positive electrode material.

[0013] In the step (1), the system is heated at a heating rate of 5-10°C / min.

[0014] In the step (2), the system is heated at a heating rate of 10-25°C / min; the weight ratio of the pore-forming agent to the carbonized material is 1:1 to 3:1.

[0015] The pore-forming agent is one or more of potassium hydroxide, sodium hydroxide, potassium carbonate and zinc chloride.

[0016] After the pore-forming treatment in step (2), the material is washed with dilute hydrochloric acid, then washed with deionized water until neutral, dried, and ball-milled to obtain a porous carbon material with a high specific surface area.

[0017] In the step (3), the system is heated at a heating rate of 20-50°C / min.

[0018] The positive electrode material precursor is petroleum asphalt and / or coal asphalt, and the softening point is 75°C to 95°C.

[0019] The specific surface area of ​​the high specific surface area porous carbon obtained in step (2) is 1000 to 2500 m 2 / g.

[0020] An application of the supercapacitor positive electrode material, and an application of the positive electrode material in a supercapacitor.

[0021] A lithium titanate-based supercapacitor, wherein the positive electrode material is the positive electrode material described above.

[0022] The advantages and positive effects of the present invention are:

[0023] The present invention provides a supercapacitor positive electrode material, which has a porous carbon pore structure to provide a fast ion transmission channel, which is beneficial to the power performance of the supercapacitor, and a microcrystalline structure of a graphite material. The specific capacity is 100-150 mAh / g, and the electronic conductivity is 5-10 S / cm, which is much higher than the specific capacity of 50 mAh / g and the electronic conductivity of 0.8 S / cm of the porous carbon positive electrode materials used in existing double-layer supercapacitors and lithium-ion supercapacitors. When matched with a lithium titanate negative electrode (specific capacity of 160 mAh / g), the lithium titanate-based supercapacitor of the present invention can greatly reduce the difficulty of coating the electrode material on the current collector caused by the matching of the positive and negative electrode capacities, and at the same time synergistically improve the energy density and power density. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Attached Figure 1 Raman image of the positive electrode material prepared in Example 1

[0025] Attached Figure 2 Raman image of the positive electrode material prepared in Comparative Example 1 DETAILED DESCRIPTION

[0026] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.

[0027] Example 1

[0028] (1) Preparation of positive electrode materials

[0029] Carbonization: Take the cathode material precursor petroleum asphalt, whose softening point is 80°C, place it in a medium-temperature furnace protected by inert gas, heat it to 650°C at a rate of 5°C / min, stay for 1 hour, cool it down and take it out to obtain the petroleum asphalt carbonized material;

[0030] Pore ​​formation: dissolve the pore-forming agent potassium hydroxide in deionized water to form a pore-forming agent solution, stir and disperse the above-obtained petroleum asphalt carbonized material in the pore-forming agent solution and fully immerse it, wherein the weight ratio of the pore-forming agent potassium hydroxide to the petroleum asphalt carbonized material is 2:1, and then place it in a medium-temperature furnace protected by inert gas, and heat it to 800°C at a rate of 10°C / min, stay for 1 hour, cool it, wash it with dilute hydrochloric acid, and then wash it with deionized water until it is neutral, dry it, and ball mill it to obtain a petroleum asphalt-based porous carbon material. It has been determined that the specific surface area of ​​the petroleum asphalt porous carbon obtained at this time is 1820m 2 / g;

[0031] High temperature treatment: The obtained porous carbon material is placed in a high temperature furnace protected by inert gas, heated to 1800°C at a rate of 20°C / min, and kept for 0.5h. After cooling, it is taken out and then graded by a cyclone separator to obtain a petroleum asphalt-based positive electrode material.

[0032] It has been determined (see Figure 1 ), the particle size D50 of the petroleum asphalt-based positive electrode material obtained at this time is 5 μm, and the specific surface area is 246 m 2 / g, Raman spectrum test shows that the intensity ratio of the disordered D peak of the positive electrode material to the ordered G peak is D / I G is 0.95, and the X-ray diffraction test shows that the ordered stacking height L of the carbon material crystallite along the z-axis direction calculated by the half-peak width of the (002) peak is CThe average width La of the carbon material crystallites along the a-axis direction calculated from the (100) peak is 15.7 nm, and the electronic conductivity is 8.7 S / cm.

[0033] The obtained petroleum asphalt-based positive electrode material was mixed with the conductive agent acetylene black and the binder polyvinylidene fluoride in a weight ratio of 0.95kg:0.025kg:0.025kg, and then 0.49kg of solvent N-methylpyrrolidone was added to form a slurry. The slurry was coated on the current collector, and after drying, it was punched into circular positive electrode sheets, assembled with metal lithium negative electrode sheets and a separator between the positive and negative electrode sheets, and injected with electrolyte to obtain a button battery. The charge and discharge test showed that the lithium insertion specific capacity of the material at a current rate of 0.2C was 120mAh / g.

[0034] (2) The petroleum asphalt-based positive electrode material obtained above is used in lithium titanate-based supercapacitors.

[0035] Positive electrode sheet: The obtained petroleum asphalt-based positive electrode material, conductive agent acetylene black, and binder polyvinylidene fluoride are stirred and mixed at a weight of 95kg:2.5kg:2.5kg, and 49kg of solvent N-methylpyrrolidone mixture is added to form a positive electrode slurry. The positive electrode slurry is applied to the current collector, dried, rolled, and cut into pieces with a size of 20.1cm×15.1cm. After vacuum baking, a positive electrode sheet is formed.

[0036] Negative electrode sheet: The negative electrode active material lithium titanate / carbon composite material, the conductive agent acetylene black, and the binder polyvinylidene fluoride are stirred and mixed at a weight of 96kg:2kg:2kg, and 122kg of solvent N-methylpyrrolidone is added to prepare the negative electrode slurry, and the negative electrode slurry is applied to the current collector, dried, rolled, and cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to form a non-pre-lithiated lithium titanate-based negative electrode sheet. The non-pre-lithiated lithium titanate-based negative electrode sheet is separated from the lithium auxiliary electrode by a diaphragm and placed in an electrolyte, and then the non-pre-lithiated lithium titanate-based negative electrode sheet and the lithium auxiliary electrode are respectively connected to a charge and discharge instrument, and discharged at a current rate of 0.2C to embed lithium ions into the non-pre-lithiated lithium titanate-based negative electrode sheet to form a pre-lithiated lithium titanate-based negative electrode sheet.

[0037] At this time, the loading amount of the slurry in the positive electrode sheet on the current collector is 15.0 mg / cm 2 The loading amount of the slurry on the current collector in the negative electrode sheet is 16.9 mg / cm 2 The capacity ratio of the negative electrode to the positive electrode is 1.5, and the design capacity of the capacitor unit is 20Ah.

[0038] Assembly: stack the sheets in the order of positive sheet / / diaphragm / / negative sheet / / diaphragm / / positive sheet / / diaphragm / / negative sheet / / diaphragm / / positive sheet... to form a winding core, and the outermost two sides of the winding core always remain positive sheets.

[0039] Liquid injection and sealing: After the core is vacuum dried, it is placed in a shell, and electrolyte is injected into the shell and sealed to obtain a lithium titanate-based supercapacitor.

[0040] (3) Lithium titanate-based supercapacitor test: After testing, the lithium titanate-based supercapacitor obtained above has a single cell capacity of 20.5 Ah at a current rate of 1C, a mass energy density of 106.8 Wh / kg, a volume energy density of 160.4 Wh / L, a power density of 6.8 kW / kg at a current rate of 10C, and a capacity retention rate of 85.8% after 50,000 continuous charge and discharge cycles at a current rate of 10C.

[0041] Example 2

[0042] In Example 1, the high temperature treatment temperature is changed to 2200° C., and the rest is the same as Example 1.

[0043] The particle size D50 of the petroleum asphalt-based cathode material obtained at this time was measured to be 4.9 μm, and the specific surface area was 185 m 2 / g, Raman spectrum test shows that the intensity ratio of the disordered D peak of the positive electrode material to the ordered G peak is I D / I G The X-ray diffraction test shows that the ordered stacking height L of the carbon material crystallite along the z-axis direction calculated by the half-peak width of the (002) peak is C The average width La of the carbon material crystallites along the a-axis calculated from the (100) peak is 18.6 nm, and the electronic conductivity is 9.5 S / cm. The button cell assembly method is the same as that in Example 1. The charge and discharge test shows that the lithium insertion capacity of the material at a current rate of 0.2C is 140 mAh / g.

[0044] After testing, the assembled lithium titanate-based supercapacitor has a single cell capacity of 20.6Ah at a current rate of 1C, a mass energy density of 106.9Wh / kg, a volume energy density of 176.8Wh / L, a power density of 6.6kW / kg at a current rate of 10C, and a capacity retention rate of 86.7% after 50,000 continuous charge and discharge cycles at a current rate of 10C.

[0045] Example 3

[0046] In Example 1, the high temperature treatment temperature is changed to 1600° C., and the rest is the same as Example 1.

[0047] The particle size D50 of the petroleum asphalt-based cathode material obtained at this time was measured to be 5 μm, and the specific surface area was 289.5 m 2 / g, Raman spectrum test shows that the intensity ratio of the disordered D peak of the positive electrode material to the ordered G peak is D / IG The X-ray diffraction test shows that the ordered stacking height L of the carbon material crystallite along the z-axis direction calculated by the half-peak width of the (002) peak is C The average width La of the carbon material crystallites along the a-axis calculated from the (100) peak is 8.9 nm, and the electronic conductivity is 5.4 S / cm. The same button cell assembly method as in Example 1 is used, and the charge and discharge test shows that the lithium insertion specific capacity of the material at a current rate of 0.2C is 114 mAh / g.

[0048] After testing, the single cell capacity of the lithium titanate-based supercapacitor obtained above is 20.5Ah at 1C rate current, the mass energy density is 106.2Wh / kg, the volume energy density is 150.8Wh / kg, the power density is 6.1kW / kg at 10C rate current, and the capacity retention rate is 84.3% after 50,000 continuous charge and discharge cycles at 10C rate current.

[0049] Example 4

[0050] In Example 1, the positive electrode material precursor is replaced with coal tar pitch, and the softening point is 85° C., and the rest is the same as Example 1.

[0051] The specific surface area of ​​the porous coal tar carbon obtained after pore formation is 1783m 2 / g, the particle size D50 of the coal tar pitch-based positive electrode material obtained after high temperature treatment is 8 μm, and the specific surface area is 212 m 2 / g, Raman spectrum test shows that the intensity ratio of the disordered D peak of the positive electrode material to the ordered G peak is D / I G The X-ray diffraction test shows that the ordered stacking height L of the carbon material crystallite along the z-axis direction calculated by the half-peak width of the (002) peak is 0.93. C The average width La of the carbon material crystallites along the a-axis calculated from the (100) peak is 14.6 nm, and the electronic conductivity is 7.5 S / cm. The same button cell assembly method as in Example 1 is used, and the charge and discharge test shows that the lithium insertion specific capacity of the material at a current rate of 0.2C is 118 mAh / g.

[0052] After testing, the single cell capacity of the lithium titanate-based supercapacitor obtained above is 20.3Ah at 1C rate current, the mass energy density is 104.6Wh / kg, the volume energy density is 158.4Wh / L, the power density is 6.7kW / kg at 10C rate current, and the capacity retention rate is 85.4% after 50,000 continuous charge and discharge cycles at 10C rate current.

[0053] Comparative Example 1

[0054] In Example 1, the high temperature treatment temperature is changed to 2800° C., and the rest is the same as Example 1.

[0055] The particle size D50 of the petroleum asphalt-based cathode material obtained at this time was measured to be 3.7 μm, and the specific surface area was 68 m 2 / g, Raman spectrum test shows that the intensity ratio of the disordered D peak of the positive electrode material to the ordered G peak is D / I G The X-ray diffraction test shows that the ordered stacking height L of the carbon material crystallite along the z-axis direction calculated by the half-peak width of the (002) peak is C The average width La of the carbon material crystallites along the a-axis calculated from the (100) peak is 27.9 nm, and the electronic conductivity is 11.5 S / cm. The same button cell assembly method as in Example 1 is used, and the charge and discharge test shows that the lithium insertion specific capacity of the material at a current rate of 0.2C is 187 mAh / g.

[0056] After testing, the single cell capacity of the lithium titanate-based supercapacitor obtained above is 20.4Ah at 1C rate current, the mass energy density is 106.7Wh / kg, the volume energy density is 190.4Wh / L, the power density is 4.3kW / kg at 10C rate current, and the capacity retention rate is 73.5% after 50,000 continuous charge and discharge cycles at 10C rate current.

[0057] Comparative Example 2

[0058] The high temperature treatment process in Example 1 was removed, and the specific capacity of the petroleum asphalt porous carbon obtained at this time was measured to be 49.5 mAh / g;

[0059] (1) The petroleum pitch porous carbon obtained above was used for lithium titanate-based supercapacitors and assembled according to the method described in Example 1.

[0060] Positive electrode sheet: the obtained petroleum asphalt porous carbon, conductive agent and binder are stirred and mixed, a solvent is added to adjust the viscosity to form a positive electrode slurry, the positive electrode slurry is coated on the current collector, dried, rolled, cut into pieces, and vacuum baked to form a positive electrode sheet.

[0061] Negative electrode sheet: The negative electrode active material lithium titanate / carbon composite material, conductive agent, and binder are stirred and mixed, and a solvent is added to prepare a negative electrode slurry. The negative electrode slurry is applied to the current collector, dried, rolled, cut, and vacuum baked to form a non-pre-lithiated lithium titanate-based negative electrode sheet. This non-pre-lithiated lithium titanate-based negative electrode sheet is separated from the lithium auxiliary electrode by a diaphragm and placed in an electrolyte. Then, the non-pre-lithiated lithium titanate-based negative electrode sheet and the lithium auxiliary electrode are connected to a charge and discharge instrument respectively, and discharged at a current rate of 0.2C to embed lithium ions into the non-pre-lithiated lithium titanate-based negative electrode sheet to form a pre-lithiated lithium titanate-based negative electrode sheet.

[0062] At this time, the loading amount of the slurry in the positive electrode sheet on the current collector is 10 mg / cm 2 The loading amount of the slurry on the current collector in the negative electrode sheet is 9.375 mg / cm 2 At this time, the capacity ratio of the negative electrode sheet to the positive electrode sheet is 3, and the maximum capacity of the capacitor cell can only be designed to 8Ah. If the design capacity is 20Ah as in the aforementioned embodiment, the specific capacity of the petroleum asphalt-based porous carbon is too low, resulting in the coating thickness of the positive electrode being too large, and ultimately causing the core composed of the positive electrode sheet, the diaphragm, and the negative electrode sheet to be too thick and unable to be packaged.

[0063] Assembly: Stack the sheets in the order of positive electrode sheet / / diaphragm / / negative electrode sheet / / diaphragm / / positive electrode sheet / / diaphragm / / negative electrode sheet / / diaphragm / / positive electrode sheet... to form a winding core, and the outermost two sides of the winding core always remain positive electrode sheets.

[0064] Liquid injection and sealing: After the core is vacuum dried, it is placed in a shell, and electrolyte is injected into the shell and sealed to obtain a lithium titanate-based supercapacitor.

[0065] (3) Lithium titanate-based supercapacitor test: After testing, the lithium titanate-based supercapacitor obtained above has a single cell capacity of 8.1 Ah at a current rate of 1C, a mass energy density of 48.5 Wh / kg, a volume energy density of 44.5 Wh / L, a power density of 4.3 kW / kg at a current rate of 10C, and a capacity retention rate of 73.8% after 50,000 continuous charge and discharge cycles at a current rate of 10C.

[0066] Comparative Example 3

[0067] (1) Preparation of positive electrode materials

[0068] Carbonization: Take the cathode material precursor petroleum asphalt, whose softening point is 80°C, place it in a medium-temperature furnace protected by inert gas, heat it to 650°C at a rate of 5°C / min, stay for 1 hour, cool it down and take it out to obtain the petroleum asphalt carbonized material;

[0069] Pore ​​formation: dissolve the pore-forming agent potassium hydroxide in deionized water to form a pore-forming agent solution, stir and disperse the above-obtained petroleum asphalt carbonized material in the pore-forming agent solution and fully immerse it, wherein the weight ratio of the pore-forming agent potassium hydroxide to the petroleum asphalt carbonized material is 2:1, and then place it in a medium-temperature furnace protected by inert gas, and heat it to 800°C at a rate of 10°C / min, stay for 1 hour, cool it, wash it with dilute hydrochloric acid, and then wash it with deionized water until it is neutral, dry it, and ball mill it to obtain a petroleum asphalt-based porous carbon material. It has been determined that the specific surface area of ​​the petroleum asphalt porous carbon obtained at this time is 1820m 2 / g;

[0070] Catalytic graphitization treatment: dissolve the graphitization catalyst ferric nitrate in deionized water to form a graphitization catalyst solution, stir and disperse the obtained porous carbon material in the catalyst solution to fully immerse it, then place it in a medium-temperature furnace protected by inert gas, heat it to 900°C at a rate of 10°C / min, stay for 2 hours, cool it, take it out, wash it with a dilute hydrochloric acid solution, and then vacuum dry it to obtain a petroleum asphalt positive electrode material.

[0071] It has been determined (see Figure 2 ), the particle size D50 of the petroleum asphalt-based positive electrode material obtained at this time is 10 μm, and the specific surface area is 1246 m 2 / g, Raman spectrum test shows that the intensity ratio of the disordered D peak of the positive electrode material to the ordered G peak is D / I G The X-ray diffraction test shows that the ordered stacking height L of the carbon material crystallite along the z-axis direction calculated by the half-peak width of the (002) peak is C The average width La of the carbon material crystallites along the a-axis direction calculated from the (100) peak is 8.6 nm, and the electronic conductivity is 2.1 S / cm. The obtained petroleum asphalt-based positive electrode material is mixed with the conductive agent acetylene black, the binder polyvinylidene fluoride, and the solvent N-methylpyrrolidone to form a slurry, which is coated on the current collector, and after drying, it is punched into a circular positive electrode sheet, assembled with a metal lithium negative electrode sheet and a separator between the positive and negative electrode sheets, and injected with an electrolyte to obtain a button battery. The charge and discharge test shows that the lithium insertion specific capacity of the material at a current rate of 0.2C is 87 mAh / g.

[0072] (2) The petroleum asphalt-based positive electrode material obtained above was used for a lithium titanate-based supercapacitor and assembled according to the method described in Example 1.

[0073] Positive electrode sheet: the obtained petroleum asphalt-based positive electrode material, conductive agent acetylene black, and binder polyvinylidene fluoride are stirred and mixed, and solvent N-methylpyrrolidone is added to adjust the viscosity to form a positive electrode slurry, and the positive electrode slurry is coated on the current collector, dried, rolled, cut, and vacuum baked to form a positive electrode sheet.

[0074] Negative electrode sheet: The negative electrode active material lithium titanate / carbon composite material, the conductive agent acetylene black, and the binder polyvinylidene fluoride are stirred and mixed, and the solvent N-methylpyrrolidone is added to prepare the negative electrode slurry, and the negative electrode slurry is applied to the current collector, dried, rolled, cut, and vacuum baked to form a non-pre-lithiated lithium titanate-based negative electrode sheet. The non-pre-lithiated lithium titanate-based negative electrode sheet is separated from the lithium auxiliary electrode by a diaphragm and placed in an electrolyte. Then, the non-pre-lithiated lithium titanate-based negative electrode sheet and the lithium auxiliary electrode are connected to the charge and discharge instrument respectively, and discharged at a current rate of 0.2C to embed lithium ions into the non-pre-lithiated lithium titanate-based negative electrode sheet to form a pre-lithiated lithium titanate-based negative electrode sheet.

[0075] At this time, the loading amount of the slurry in the positive electrode sheet on the current collector is 10.0 mg / cm 2 The loading amount of the slurry on the current collector in the negative electrode sheet is 8.7 mg / cm 2 The capacity ratio of the negative electrode to the positive electrode is 1.6, and the design capacity of the capacitor unit is 20Ah.

[0076] Assembly: stack the sheets in the order of positive sheet / / diaphragm / / negative sheet / / diaphragm / / positive sheet / / diaphragm / / negative sheet / / diaphragm / / positive sheet... to form a winding core, and the outermost two sides of the winding core always remain positive sheets.

[0077] Liquid injection and sealing: After the core is vacuum dried, it is placed in a shell, and electrolyte is injected into the shell and sealed to obtain a lithium titanate-based supercapacitor.

[0078] (3) Lithium titanate-based supercapacitor test: After testing, the lithium titanate-based supercapacitor obtained above has a single cell capacity of 20.3 Ah at a current rate of 1C, a mass energy density of 75.8 Wh / kg, a volume energy density of 90.4 Wh / L, a power density of 3.4 kW / kg at a current rate of 10C, and a capacity retention rate of 73.5% after 50,000 continuous charge and discharge cycles at a current rate of 10C.

[0079] The above-mentioned embodiments only represent several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.

Claims

1. A supercapacitor positive electrode material, characterized in that: The positive electrode material is a carbon material with pores and microcrystalline structure, with a particle size D50 of 2 to 8 μm and a specific surface area of ​​50 to 300 m 2 / g, in the Raman spectrum, the intensity ratio of the disordered D peak to the ordered G peak is D / I G is 0.9 to 1.1, and the ordered stacking height L of the carbon material crystallites along the z-axis direction calculated from the half-peak width of the (002) peak in the X-ray diffraction pattern C The carbon material has an average crystallite width La of 3 to 10 nm along the a-axis direction calculated from the (100) peak, a specific capacity of 100 to 150 mAh / g, and an electronic conductivity of 5 to 10 S / cm.

2. The supercapacitor positive electrode material according to claim 1, characterized in that: The positive electrode material is a carbon material having pores and a microcrystalline structure formed by carbonizing a precursor material, forming pores and undergoing high-temperature treatment.

3. The supercapacitor positive electrode material according to claim 2, characterized in that: (1) Carbonization: The cathode material precursor is placed in a medium temperature furnace protected by an inert gas at 500-700°C for carbonization for 0.5-2 hours, and then taken out after cooling to obtain a carbonized material; (2) Pore formation: the pore former is dissolved in deionized water to form a pore former solution, the carbonized material is stirred and dispersed in the pore former solution and fully impregnated, and then placed in a medium temperature furnace protected by inert gas at 600-800°C for 0.5-2h, cooled, washed and dried to obtain a porous carbon material with a high specific surface area; (3) High temperature treatment: The obtained porous carbon material is placed in a high temperature furnace protected by inert gas at 1600-2200°C for 0.5-2h. After cooling, it is taken out and then graded by a cyclone separator to obtain a positive electrode material.

4. The supercapacitor positive electrode material according to claim 3, characterized in that: In the step (1), the system is heated at a heating rate of 5-10°C / min.

5. The supercapacitor positive electrode material according to claim 3, characterized in that: In the step (2), the system is heated at a heating rate of 10-25°C / min; The weight ratio of the pore former to the carbonized material is 1:1 to 3:

1.

6. The supercapacitor positive electrode material according to claim 3, characterized in that: The pore-forming agent is one of potassium hydroxide, sodium hydroxide, potassium carbonate and zinc chloride.

7. The supercapacitor positive electrode material according to claim 3, characterized in that: In the step (3), the system is heated at a heating rate of 20-50°C / min.

8. The supercapacitor positive electrode material according to claim 2 or 3, characterized in that: The positive electrode material precursor is petroleum asphalt and / or coal asphalt.

9. An application of the supercapacitor positive electrode material according to claim 1, characterized in that: Application of the positive electrode material in supercapacitors.

10. A lithium titanate-based supercapacitor, characterized in that: The positive electrode material is the positive electrode material according to claim 1.